A Single Centric, Open-Label, Non-Randomized Post- Marketing Surveillance Study to Measure the Efficacy and Safety of Petsaffa Tablets in Subjects Suffering From Constipation, Gas and Acidity (International Journal of Ayurveda and Pharma Research, 2024)
Constipation, gas, and acidity are common gastrointestinal issues with a significant global prevalence. Traditional medicine systems like Ayurveda have long utilized medicinal plants to address these concerns. However, clinical validation of their efficacy in patients with constipation has been lacking. Objectives: This study aimed to assess the efficacy and safety of Petsaffa tablets, an Ayurvedic formulation containing various herbal ingredients, in relieving constipation, gas, and acidity. Methods: The study, conducted as a single-centric, open-label, non-randomized post-marketing surveillance study, involved 120 subjects with constipation. Subjects were evaluated using inclusion and exclusion criteria and provided Petsaffa tablets for a 14-day intervention. Various parameters, including bowel movement frequency, constipation scores, and subjective assessments, were measured. Vital signs, laboratory safety parameters, and adverse events were also monitored during the study period. Results: Petsaffa tablets significantly improved bowel movement frequency, constipation scores, and subjective symptoms related to constipation. Stool consistency and other associated symptoms such as acidity and gas were also reduced at the end of the study. None of the participants reported any adverse events, and safety parameters remained within normal limits during the study period. Conclusion: Petsaffa tablets offer a promising, safe, and effective alternative option for individuals with common gastrointestinal issues such as constipation, acidity, and gas.